Combining Electrodermal Activity With the Peak-Pain Time to Quantify Three Temporal Regions of Pain Experience - Bhatkar, Viprali; Picard, Rosalind; Staahl, Camilla (Frontiers in Pain Research, 2022)
Background: Self-reported pain levels, while easily measured, are not reliable or repeatable for quantifying pain. Objective methods are needed that supplement self-report without adding undue burden or cost to a study. Methods that integrate multiple measures, such as combining self-report with physiology in a structured and specific-to-pain protocol may improve measures. Method: We propose and study a novel method that combines the timing of the peak pain measured by an electronic visual-analog-scale (eVAS) with the continuously-measured electrodermal response (EDR), a physiological measure quantifying sympathetic nervous system activity that is easily recorded with a skin-surface sensor. The new pain measure temporally isolates and specifically quantifies three phases of dynamic pain experience: I. Anticipation preceding onset of a pain stimulus, II. Rise to peak pain, and III. Recovery from peak pain level. We evaluate the combined EDR and eVAS across two types of pain (cold pressor, capsaicin), and four types of treatments (none, A=pregabalin, B=oxycodone, C=placebo). Each of 24 patients made four visits within 8 weeks, for 96 visits total: A training visit (TV), followed by three visits (randomized), each double-blind presenting A, B, or C. Within each visit, the participant experienced two segments (cold pressor, cold pressor followed by capsaicin) of painful stimuli, separated by a one-hour rest period, during which one of the four treatments was provided. Results: The novel method specifically and successfully discriminates the two different pain models and four treatments, confirming maximal pain for no-treatment, followed by mild pain reduction for placebo, followed by the most pain reduction with analgesics. The new objective measure also maintains significant discrimination across the different test conditions both within a single-day’s visit (for relative pain relief within a visit) and also across repeated visits spanning weeks (reducing different-day-physiology affects). Conclusion: The new method combines the time of peak pain with the advantage of continuous physiological data to objectively capture and quantify the sympathetic nervous system response preceding and following that peak. The method provides both a specific and sensitive means of accurately discriminating different levels of pain experience for both pain models including reduction of pain with clinically effective analgesics.